1997
DOI: 10.1007/s001250050820
|View full text |Cite
|
Sign up to set email alerts
|

Chronic central neuropeptide Y infusion in normal rats: status of the hypothalamo-pituitary-adrenal axis, and vagal mediation of hyperinsulinaemia

Abstract: Summary Neuropeptide Y in the hypothalamus is a potent physiological stimulator of feeding, and may contribute to the characteristic metabolic defects of obesity when hypothalamic levels remain chronically elevated. Since corticosterone and insulin are importantJJregulators of fuel metabolism, the longitudinal effects of chronic (6 days) intracerebroventricular infusion of neuropeptide Y in normal rats on the hypothalamo-pituitary-adrenal axis and on insulin secretion were studied. Neuropeptide Y-infused rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 45 publications
6
86
0
Order By: Relevance
“…It is not known whether such changes are induced by dexamethasone. Nevertheless, our conclusion supports previous reports on animal studies of a neural contribution to insulin hypersecretion in insulin resistance [13,14,26,27]. Our study seems, however, to contradict a recent study of insulin-resistant Pima Indians in which the high PP response but not the high insulin response to meal ingestion was reduced by cholinergic antagonism by atropine [35].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…It is not known whether such changes are induced by dexamethasone. Nevertheless, our conclusion supports previous reports on animal studies of a neural contribution to insulin hypersecretion in insulin resistance [13,14,26,27]. Our study seems, however, to contradict a recent study of insulin-resistant Pima Indians in which the high PP response but not the high insulin response to meal ingestion was reduced by cholinergic antagonism by atropine [35].…”
Section: Discussionsupporting
confidence: 66%
“…Previously such a hypothesis has been restricted to experimental animals. Thus, cholinergic antagonism by muscarinic receptor antagonists or truncal vagotomy reduces hyperinsulinaemia in insulin-resistant ob/ ob mice [13], fa/fa rats [26] or rats with experimental lesion in the ventromedial hypothalamus [14,27]. In humans, we previously reported that the plasma PP level, which is considered an indirect marker of parasympathetic activity [16,17], is negatively correlated to insulin sensitivity over a large range of insulin sensitivity [3].…”
Section: Discussionmentioning
confidence: 99%
“…Body weight after 6 days of infusion: Normal + ICV vehicle, 407 ± 8 g; Normal + ICV NPY, 382 ± 7 g; ADX + ICV vehicle, 385 ± 13 g; ADX + ICV NPY, 421 ± 15 g, n = 4-11 rats per group, NS. This is consistent with data showing that, whereas chronic central NPY infusion significantly increases body weight in ad libitum--fed rats, no such increase is observed when NPY--induced hyperphagia is prevented by pair--feeding with vehicle--infused controls [30,46]. In sham--operated normal rats, 7--day central NPY infusion (15 µg/day in 24 µl) increased adiposity, as shown by the significant increases in epididymal white adipose tissue (WATe) weight (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Of all of these peptides however, NPY is one of the few which actually leads to the development of true obesity and insulin resistance when hypothalamic levels remain chronically elevated [3,28,30,33,40,46,47], as has been reported for various rodent genetic obesity syndromes [2,8,35,42]. The obesity syndrome which results from chronically elevated hypothalamic NPY levels in rodents [3,28,30,33,40,46,47] is still present even when NPY--induced hyperphagia is prevented [3,30,46], demonstrating that hyperphagia is not necessary for central NPY to produce its obesity--like effects. NPY in the hypothalamus is also involved in the regulation of several other important physiological processes including growth [4,22,25], reproduction [4,5,25], and fluid balance [13].…”
Section: Introductionmentioning
confidence: 99%
“…In keeping with this, body weight was not affected when haloperidol was administered orally to male rats for three or six weeks (Minet-Ringuet et al, 2005 andPouzet et al, 2003), and was even suppressed under the longer treatment period of 80 weeks (Yoshida et al, 1995). The early stages of obesity, indicated by an increase in percent body fat, have been observed even in the absence of increases in body weight or food intake (Kushi et al, 1998, Pedrazzini et al, 1998and Sainsbury et al, 1997. This is due to preferential channelling of fuels from lean tissues such as muscle and bone towards white This study examined the effects of chronic subcutaneous infusion of supratherapeutic doses of a typical (haloperidol) and an atypical (risperidone) antipsychotic drugs on endocrine functions and metabolic profile in male SpragueeDawley axes (testosterone), the two antipsycho on endocrine activities, with haloperido insulin levels and risperidone incre levels.…”
Section: Effect Of Haloperidol or Risperidone On Body Tissue Compositionmentioning
confidence: 65%